Preservation of Electronic Records in Selected Federal Universities in Nigeria - ABDULKADIR, AHMED IDRIS (MiddleBelt Journal of Library and Information Science, 2020)
The paper examines how federal universities in Nigeria preserve their electronic records, including erecords preservation strategies, ICT skills of staff and ICT facilities that are available for e-records preservation. The study adopted quantitative approach through cross-sectional survey design to administer questionnaire on the population of one hundred and fifty one (151) staff of the Management Information System/Registry departments drawn from twelve (12) Federal Universities. Eighty four (84) staff were used as the subject for the study. Descriptive statistics was used to analyse the data collected for the study. The study found that Federal Universities in Nigeria were not preserving their electronic records effectively due to lack of ICT facilities, technical skills of staff and e-records preservation policy. The study also found that staff preserving e-records had never attended any form of staff training and development programme. The study recommends the establishment of policy framework on e-records preservation, provision of adequate and up to date ICT facilities, training of e-records personnel, provision of e-records management framework and infrastructure. The originality of the study lies in its ability to exposed Nigerian Universities to the global best practices in e-records preservation.